2010
DOI: 10.1111/j.1745-4514.2009.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSING ABSORBABILITY OF BIOACTIVE COMPONENTS IN ALOE USINGIN VITRODIGESTION MODEL WITH HUMAN INTESTINAL CELL

Abstract: This study used a simulated in vitro digestion model coupled with caco‐2 cell to assess the digestive stability and absorption of aloin, aloe‐emodin and aloenin A. Aloenin A and aloe‐emodin were stable and entirely recovered during simulated digestion, but 50% of aloin was lost. Approximately 53.2, 7.3 and 28.7% of aloe‐emodin, aloenin A and aloin, respectively, was transported into both apical and basolateral compartments after 1 h incubation in caco‐2 cell. The involvement of several transporter proteins for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…It was reported that primary pharmacological activity of phlorizin was to inhibit the sodium‐glucose symporters found in the small intestinal membrane, blocking intestinal glucose absorption (Ehrenkranz and others ). Phloridzin as a competitive inhibitor of SGLT1 was coincubated with SMM for evaluating involved transport mechanism (Vaidyanathan and Walle ; Shim and Kwon ). In order to examine whether SMM is a substrate for SGLT1 transporter or not, cellular uptake of SMM by Caco‐2 cells was determined by incubation with SGLT1 competitive inhibitor such as a phloridzin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that primary pharmacological activity of phlorizin was to inhibit the sodium‐glucose symporters found in the small intestinal membrane, blocking intestinal glucose absorption (Ehrenkranz and others ). Phloridzin as a competitive inhibitor of SGLT1 was coincubated with SMM for evaluating involved transport mechanism (Vaidyanathan and Walle ; Shim and Kwon ). In order to examine whether SMM is a substrate for SGLT1 transporter or not, cellular uptake of SMM by Caco‐2 cells was determined by incubation with SGLT1 competitive inhibitor such as a phloridzin.…”
Section: Resultsmentioning
confidence: 99%
“…Bioavailability is normally described as the potential amount of components in food matrix, which can be available into body (Ekmekcioglu ; Laparra and others ; Shim and Kwon ). Caco‐2 cell lines as a model of human intestines have been well recognized to predict the bioavailability of bioactive components in utilized food matrix or plants (Ekmekcioglu ; Laparra and others ; Shim and Kwon ; Yang and others ). For increasing the bioavailability of SMM, it is important to understand its intestinal transport mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that an in vitro digestion model system simulating human digestive fluids could support reliable prediction of bioavailability or transport mechanism of polyphenols in various plants (Shim and Kwon 2010a,b).…”
Section: Introductionmentioning
confidence: 92%
“…If there is an increase in the rates of elimination of blood alcohol throughout the body were originate with the treatment of barbaloin. Pretreatments with the help of can results in decrease the level of blood alcohol (Area under curve) and there is an increase in the rate of departure of ethanol [36]. To evaluate the digestive constancy or in the absorption of barbaloin with other aloe constituents, the in vitro model fitted with cancer coli-2cell was used in the current identification.…”
Section: Impact On Metabolism and Bioavailabilitymentioning
confidence: 99%